Strategy for Maximizing MSME Profits Amid Increases in Fuel Prices from the Perspective of Maqashid Syariah Asy-Syatibi - Muafi Aulia Rachman; Lilik Rahmawati; Nur Diana Khalida (Universitas Islam Balitar, 2023)
Energy is a very important part in the life of the world community in general and the Indonesian people in particular. Almost all sectors in this life (industry, households, transportation, services, etc.) cannot be separated from the energy sector, especially fuel oil (BBM). Fuel is a commodity that plays a vital role in all economic activities. The direct impact that can be felt from the increase in fuel prices is changes in operating costs that result in changes in the level of profits or losses. This study aims to determine the profit maximization strategy carried out by MSMEs amid the increase in fuel prices and is reviewed with the perspective of Asy-Syatibi sharia maqashid. This type of research is qualitative research with a descriptive approach, with data sources obtained from interviews with MyAlpucok business owners and literature studies. The results showed that the strategy carried out by MSMEs was carried out in accordance with the concept of maqashid sharia, where MSME actors carried out a strategy of maximizing their business profits by running in accordance with Islamic sharia that had been taught by Allah and the Messenger of Allah.